Carotid sinus nerve stimulation in the management of intractable angina pectoris: four-year follow-up - Rotem, C. Eve (1974)
Since February 1969 carotid sinus nerve stimulators have been implanted in 13 patients with intractable, incapacitating angina pectoris, unrelieved by medical management and, in some cases, revascularization procedures. Four patients died, one on the third postoperative day, the others at 15, 31 and 49 months postoperatively. Two other patients sustained myocardial infarcts, at two weeks and two months postoperatively. Complications were few and transient. The condition of two patients is now deteriorating. In all cases there was relief of pain and a decrease in blood pressure and heart rate. Exercise could be performed at a heavier load or for a longer time. Use of the stimulator was both intermittent and continuous, proving especially valuable in the relief of nocturnal angina. All patients were markedly improved and able to leave hospital. Four patients underwent aortocoronary bypass 14, 15, 22 and 28 months after implantation of the device; three obtained good results and no longer require the CSNS although it remains in place. The fourth obtained little improvement and continues to use the stimulator.